2017
DOI: 10.1002/jrs.5100
|View full text |Cite
|
Sign up to set email alerts
|

Improved stopped‐flow time‐resolved resonance Raman spectroscopy device for studying enzymatic reactions

Abstract: An improved stopped-flow resonance Raman spectroscopy device was constructed using a stopped-flow mixer with a dead time of 3 ms and a mixing volume of 0.1 mL. The device was tested using myoglobin, where the formation reaction of a high-valent heme species, ferryl-oxo heme, was monitored by time-resolved resonance Raman spectroscopy after mixing a ferric myoglobin solution with a hydrogen peroxide solution. The ferryl-oxo heme formation rate constant obtained by Raman spectroscopy is in good agreement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…This cryo-Raman method allowed us to accumulate the specific photointermediates by controlling the temperature and observe their structural transitions based on the time-dependent Raman spectra. Because of the sufficient accumulation of the photointermediates at low temperatures, we can apply the near-IR Raman excitation to measure the spectra without the fluorescence interference or the unfavorable side products, which often complicate the interpretation of the time-resolved resonance Raman spectra ( 15 , 16 ). We successfully observed the vibrational spectra of O1, O2, and N. The spectral features indicated that O1 and O2 have the 13- cis and all- trans forms of the RSB chromophore, respectively.…”
mentioning
confidence: 99%
“…This cryo-Raman method allowed us to accumulate the specific photointermediates by controlling the temperature and observe their structural transitions based on the time-dependent Raman spectra. Because of the sufficient accumulation of the photointermediates at low temperatures, we can apply the near-IR Raman excitation to measure the spectra without the fluorescence interference or the unfavorable side products, which often complicate the interpretation of the time-resolved resonance Raman spectra ( 15 , 16 ). We successfully observed the vibrational spectra of O1, O2, and N. The spectral features indicated that O1 and O2 have the 13- cis and all- trans forms of the RSB chromophore, respectively.…”
mentioning
confidence: 99%
“…The device was tested using myoglobin, where the formation reaction of a high‐valent heme species and ferryl‐oxo heme, was monitored by time‐resolved resonance Raman spectroscopy after mixing a ferric myoglobin solution with a hydrogen peroxide solution. These results show that the new device is generally applicable to enzyme‐substrate reactions with a significantly higher time resolution than has previously been reported …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%